2018
DOI: 10.5897/ijmms2018.1357
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with atherogenic dyslipidemia among hypertensive patients at southern Ethiopia

Abstract: Atherogenic dyslipidemia worsens cardiovascular functions and supporting data concerning dyslipidemia among hypertensive patients in Ethiopian situation is very limited. The objective of this study was to assess factors associated with atherogenic dyslipidemia among hypertensive patients at Southern Ethiopia. A cross-sectional study was conducted on 238 hypertensive participants at Hawassa University comprehensive specialized hospital from September 2015 to June 2016. Systematic random sampling technique was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
5
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 29 publications
8
5
4
Order By: Relevance
“…This could be explained by as waist circumference increases energy might be stored in different forms of lipids. Contrary to the findings in many previous studies [ 9 , 15 , 16 , 18 , 28 ], BMI was not significantly associated with dyslipidemia in this study. This could be explained by the evidence that BMI was pointed as a poor indicator of obesity or body fatness in previous studies [ 34 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This could be explained by as waist circumference increases energy might be stored in different forms of lipids. Contrary to the findings in many previous studies [ 9 , 15 , 16 , 18 , 28 ], BMI was not significantly associated with dyslipidemia in this study. This could be explained by the evidence that BMI was pointed as a poor indicator of obesity or body fatness in previous studies [ 34 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of elevated LDL-C in this study, 21.5% is comparable with the study findings reported in Hawassa, southern Ethiopia, 21% [ 16 ], Africa, 21.4% [ 4 ], India, 23% [ 22 ], and Venezuela, 23.3% [ 27 ]. However, it is higher than the study findings reported in China, 8.3% [ 1 ], Ethiopia, 14.1% [ 9 ], and India, 15.8% [ 29 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations